Effects of pine invasions on ground-dwelling ants on the southern slopes of the Swartberg Mountains - Chaane, Lovejoy (FitzPatrick Institute of African Ornithology, 2023)
Ant and plant assemblages in patches of Pinus species trees in mountain fynbos and renosterbos (Elytropappus rhinocerotis) shru.bland were investigated in order to detennine whether there were differences in ant and plant species richness, abundance and cover between patches of pines and the surrounding indigenous vegetation. The study was carried out in the Matjiesrivier valley on the southern slopes of the Swartrg mountains in the Oudtshoom district, South Africa. Ants were collected at three sites: one in an older (c. 70 years) pine patch in mesic mountain fynbos at about midslope and two in younger (c. 10 years) pine patches in closed and open remnant renosterbos shrublands respectively on lower slopes. On a per site basis, there were no major differences in ant and plant species richness between the pine and no-pine sites in renosterbos, or (with the exception of plants) the pine and no-pine site in mesic mountain fynbos. A total of 2 539 ants belonging to 37 species, distributed among 15 genera, were collected during the study. Camponotus was most species-rich genus (13 species), followed by Monomorium (7 species), Tetramorium (4 species) and Lepisiota (2 species), with 11 of the 15 genera each represented by a single species. No non-indigenous species were observed during the duration of the study. Camponotus sp.11, Lepisiota sp.1 and Tetramorium quadrispinosum were observed only in the open renosterbos site. Camponotus klugii, Camponotus sp. l, Camponotus sp. 6, Cerapachys sp. l, Meranoplus peringueyi, Monomorium fri.dae, Monomoriu1'Jl sp.3 and Technomyrmex albipes were observed only in the closed renosterbos. Camponotus bayneii, Camponotus sp.5, 7, 8 and 9, Crematogaster peringueyi, Pachycondyla pumicoca, Solenopsis punctaticeps and Tetramorium regulare were recorded only in mesic mountain fynbos The most abundant ant guild was the non-dominant generalist (17 species), particularly Pheidole sp. 1# (48 % of all individual ants) followed by nectar feeders (15 species), dominant generalists (2 species), specialist predators (2 species) and a seed harvester (1 species). In general, the non-dominant generalists preferred no-pine sites to sites invaded by pines. There was very little undergrowth under the pines in mesic mountain fynbos, and Clutia polygonoides, Cymbopogon sp. 1, Erica sp. 1, Metalasia cephalotes, Metalasia muricata, Pelagronium betulinum sp. 1 and Restio sp. 1 were significantly more frequent outside the patch. The two renosterbos sites showed no significant difference in Elytropappus rhinoceroti's cover in and out of pine patches, and only two species at the open rerttsterbos site, Dodonea sp. 1 and Re/hania squarrosa, were more abundant under pines than in the surrounding renosterbos. The most abundant plant life form was the ericoids (37 species) followed by proteiods (11 species), grasses (11 species), forbs (9 species) and succulents (4 species). In general, the five life forms did not show -any exclusive pattern of preference for either the pine or no-pine sites.